Workflow Management System For Networked Device - Ngeow , Yen Churn (2009)
In this research work, the Workflow Management System (WFMS), which is typically used to manage business processes, is now introduced to manage hardware devices and task coordination. The aim of this work is therefore to design, develop and evaluate workflow system which is referred to as the Workflow Management System for Network Device (WMS-ND) in this thesis.